The importance of al-wasatiyyah in Islamic worldview - Ashimi, Tijani Ahmad (International Journal of Scientific and Research Publications, 2020)
Al wasatiyyah is Arabic word which means moderation and balance. Down the centuries, Islam provided an entire life structure that teaches man to follow the middle ground between physical and spiritual needs, balance between worldly life and hereafter and balance between Physical universe, (micro & macro- humans, flora, fauna, inanimate environments) and metaphysical cosmos (angels, heaven, hell, jinn, satan). Thus, Islam as a seal of revealed religions is a belief system that gives to each aspect of human life without any imbalance or exaggeration and never asks people to focus only on the spiritual dimension or on material aspect of their life. It means, one must not be extreme or rigid in one aspect of the world and neglect another dimension, but he should balance his routine activities and worldly affairs, (economic, religious, political and ceremonial activities) with hereafter, on the ground that Islam believes that the healthy life is highly situated in moderate life. Based on this fact, this humble paper aims to explore the importance of moderation in Islamic worldview, with particular reference to moderation in religion. However, For the sake of article, revelation based approach will be applied to carry out this study. Finally, a brief conclusion will be provided, followed by some suggestions and recommendations.